O riso irônico dos bobos da corte Guarin, de Antônio José da Silva, e Dom Bibas, de Alexandre Herculano, como desafio ao poder do Clero e da monarquia - Eustáquio, Arlene Rosa (2023)
This doctoral research aims, as a general objective, to study and approach the jester Guarin from the play "O Prodígio de Amarante" (2005), by Antônio José da Silva, the Jew, and Dom Bibas from the novel "O bobo" (1843), by Alexandre Herculano, regarding the use of humor as a mean of challenging the monarchic and clerical power and resisting the current order. Through a comparative analysis, it is evidenced how Guarin, the gracious one from Antônio José, directs his critiques towards the Catholic Church - towards religious fanaticism and the actions of the Tribunal of the Holy Office of the Inquisition - in an ironic and sarcastic way, and, parallelly, Dom Bibas, the jester from Herculano, plays a fundamental role in the political outcome that ensured Portugal's independence, using the cunningness derived from his desire for revenge after a punishment he suffered by the king's determination due to his critiques. The research seeks to understand how these jesters obtained a double function in the referenced works: to provoke laughter and, at the same time, denounce the tyranny and the flaws of character of personalities that behaved as untouchable, such as the nobles, the monarchs, the knights, and the clerics, provoking reflections about the social structures, oppressors, marked by economic and political divergences that imposed fear, silencing and controlling any attempts of change. For the theoretical foundation of this study, the contributions of Mikhail Bakhtin (1987) regarding carnivalization and the comic function of the gracious, Henri Bergson (1983) and George Minois (2003) on laughter, Linda Hutcheon (1985, 2000) about irony are of great importance. In addition to these, Carl Gustav Jung (2000, 2008) sheds light on research on the representation of the court jester archetype, especially that of Sallie Nichols (2007), also used in this thesis. Regarding the biographical study of Antônio José da Silva, the references are mainly centered on Alberto Dines (1992, 2005), Alberto Dines and Victor Eleutério (2005), Kenia Maria de Almeida Pereira (1998, 2001), and Paulo Roberto Pereira (2007). The biographical study of Alexandre Herculano is based on Cândido Beirante (1977) and António Baião (1921).